Optimalisasi Peran Lembaga Perlindungan Saksi dan Korban Dalam Memfasilitasi Pemberian Kompensasi Terhadap Korban Terorisme - Ratri, Adinda Kusumanig; Wahyudi, Slamet Tri (Bacarita Law Journal, 2024)
This research aims to examine the role of the Witness and Victim Protection Agency (LPSK) as a facilitator in providing compensation for victims of terrorism and to analyze the implementation of compensation for victims of terrorism. This research is motivated by the fact that LPSK has not been optimal in exercising its authority as a facilitator in providing compensation to victims of terrorism. The research method used is normative juridical through statute approach, namely Terrorism Law and Victim Witness Protection Law and conceptual approach. The novelty in this research is to complement the studies conducted in previous studies that analyzed using Law Number 5 of 2018 concerning Eradication of the Crime of Theorism, in this study comparing the Terrorism Law with Law Number 31 of 2014 concerning Witness and Victim Protection. As well as examining the provision of compensation to Victims of Past Terrorism (KTML). Based on the results of the research, it is concluded that LPSK has not been optimal in exercising its authority as a facilitator of compensation for victims of terrorism. However, LPSK has a breakthrough mechanism.